Unbounding the Managerial Mind: It’s Time to Abandon the Image of Managers as “Small Brains” - PORAC, Joseph (Institutional Knowledge at Singapore Management University, 2013)
Management theory has been heavily influenced by Simon’s concept of bounded rationality, so much so that bounded rationality has become a first principle in many modern theories of management and organization. But this influence has come at a price. It has devolved into a view of managers as “small brains” myopically trapped in local environments. We take issue with small-brained management theory, and argue that the time is ripe to refashion the microfoundations of managerial cognition into a “big-brained” alternative.